KETERANGAN TESTIMONIUM DE AUDITU YANG DIJADIKAN SEBAGAI ALAT BUKTI DALAM PENJATUHAN PUTUSAN HAKIM - Filzah Arina Putri; Ahmad Mahyani (Gapenas Publisher, 2023)
According to Article 1 point 26 of the Criminal Procedure Code, neither the Public Prosecutor nor Legal Counsel may present witnesses who are deemed to have met the requirements as qualified witnesses. According to Article 185 paragraph (6) letter a of the Criminal Procedure Code, one of the main factors that must be considered by the panel of judges in determining whether or not a witness' statement is true or not is the conformity between the testimony of the first witness and the statements of other witnesses. This assessment is also inseparable from the judge's conviction which will be determined by the evidence provided by the witness. Basically, the witness testimony de auditu cannot be said to be a valid witness or cannot be accepted as evidence in the evidentiary process. In the field of criminal law, the terms criminal and sentencing are used interchangeably. However, the term punishment is more precisely interpreted as